A multi-objective optimisation algorithm for rural tourism route recommendation. (21st July 2022) - Lu, Yuping
In order to solve the problems of low accuracy and lengthy time consumed in traditional rural tourism route recommendation methods, a recommendation method for rural characteristic tourism route based on multi-objective optimisation algorithm is proposed. The specific opening time, ticket price and GPS coordinates of different scenic spots are extracted to obtain the comprehensive evaluation of rural scenic spots. The optimal recommendation list is obtained by multi-objective optimisation algorithm, and the candidate set of rural characteristic tourism routes is formed through the recommendation algorithm to realise the recommendation of rural characteristic tourism routes. The experimental results show that the accuracy of the proposed method is up to 99%, the recommendation time is always less than 5.5 min, and the recommended route cost is low, which verifies the feasibility of the proposed method.